Transnational spaces, hybrid governance and civil society contestation in Mozambique's gas boom. Issue 1 (January 2016) - Symons, Kate
Abstract: This article traces a recent disruption of an on-shore gas processing plant planned by US oil and gas company Anadarko in Cabo Delgado, Mozambique. This flagship project rests on the resettlement of over 1500 people from the Afungi Peninsula. It has been contested by civil society in a high-profile legal challenge centred on land rights and consultation. The paper explores the role of gas in visions of national development, the complex position of civil society organisations and the significance of this campaign, and the practices used by Anadarko and the Government of Mozambique to produce extractive zones. The paper argues first that ideas about the hyper-modernity of gas and extractives-led national development are central to the debates over the LNG plant. Second, that the rights-based principles invoked in contestation have produced contradictory responses from Anadarko and the state. Third, that although civil society has brought about a change in behaviour by Anadarko and secured significant benefits for communities, in invoking ideas of rights and participation they legitimise the same set of principles that are central to Anadarko's claims to the land. There is currently very little critical literature on Mozambique's extractives boom, an empirical gap this paper helps to fill.